Recent advances in earth-abundant transition metal-catalyzed dihydrosilylation of terminal alkynes - Lee, Chanmi; Lee, Dohun; Hong, Sung You; Jung, Byunghyuck; Seo, Sangwon (Frontiers in Chemistry, 2024)
Over the past few years, earth-abundant transition metal-catalyzed hydrosilylation has emerged as an ideal strategy for the synthesis of organosilanes. The success in this area of research has expanded to the advancements of alkyne dihydrosilylation reactions, offering broadened synthetic applications through the selective installation of two silyl groups. In particular, catalysts based on Fe, Co, and Ni have engendered enabling platforms for mild transformations with a range of distinct regioselectivity. This mini-review summarizes recent advances in this research field, highlighting the unique features of each system from both synthetic and mechanistic perspectives.